2021
DOI: 10.1177/1178622121995847
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Current and Future Climate Change Impact on Soil Loss Rate of Agewmariam Watershed, Northern Ethiopia

Abstract: Soil erosion is 1 of the most important environmental problems that pose serious challenges to food security and the future development prospects of Ethiopia. Climate change influences soil erosion and is critical for the planning and management of soil and water resources. This study aimed to assess the current and future climate change impact on soil loss rate for the near future (2011-2040), middle future (2041-2070), and far future (2071-2100) periods relative to the reference period (1989-2018) in the Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
(74 reference statements)
2
10
0
Order By: Relevance
“…Phinzi et al [75] evaluated the use of the Durigon algorithm [76] in deriving C factor values based on NDVI for tropical areas, while Watene [47] recommended the use of LULC maps to assign C parameters in Kenya. Similar to other regional studies in other parts of the world focusing on future rainfall erosivity [3,24,50,77], the nationwide 2016 LULC map was used to obtain C coefficients to compute the present soil erosion status, as well as for the 2030s and 2080s periods. Table 3 shows C factor values used in this research, as sourced from past literature within the East Africa region.…”
Section: Slope Length and Slope Steepness (Ls) Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Phinzi et al [75] evaluated the use of the Durigon algorithm [76] in deriving C factor values based on NDVI for tropical areas, while Watene [47] recommended the use of LULC maps to assign C parameters in Kenya. Similar to other regional studies in other parts of the world focusing on future rainfall erosivity [3,24,50,77], the nationwide 2016 LULC map was used to obtain C coefficients to compute the present soil erosion status, as well as for the 2030s and 2080s periods. Table 3 shows C factor values used in this research, as sourced from past literature within the East Africa region.…”
Section: Slope Length and Slope Steepness (Ls) Factormentioning
confidence: 99%
“…The Intergovernmental Panel on Climate Change (IPCC) 2014 report [20] and recent studies projected a high 'likelihood of enhanced rainfall' in EA due to increases in the concentration of atmospheric greenhouse gases (GHG) [12,21,22]. Since almost 75% of soil erosion variation is attributed to rainfall erosivity and the terrain's slope gradient [23], the projected precipitation over EA heightens the potential level of soil loss in this tropical region [17,24]. It is thus increasingly necessary to quantify climate-driven soil erosion rates in order to formulate appropriate adaptation and conservation measures.…”
Section: Introductionmentioning
confidence: 99%
“…The IPCC regional review on climate change identified three vulnerable sectors in Ethiopia: food security, water resources, and health [19]. Natural hazards have claimed millions of lives and destroyed crops [20] as Ethiopia was highly affected by increased soil erosion [21], reduction in available water [22], and severe droughts [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Solomon et al (2021) reported that climate change will decline by 25.4%, 21.8% and 25.2% of the production of teff, maize and sorghum, respectively, by 2050 as compared to the base period in Ethiopia. Climate change also cause high soil loss and cause gully formation and change land use type (Girmay et al, 2021). The two most significant agro‐climatic factors that reduce crop productivity are often rainfall and temperature (IPCC, 2007).…”
Section: Introductionmentioning
confidence: 99%